Genetic Variability, Character Association and Path Analysis in Boro Rice (Oryza sativa L.) Germplasm from Bangladesh - Islam, MZ; Chakrabarty, T; Akter, N; Rashid, ESMH; Khalequzzaman, M; Chowdhury, MAZ (Bangladesh Rice Journal, 2019)
The success of varietal development programmme largely depends on the nature and magnitude of genetic variability, heritability and characters association of the crop. The objective of the present study was to estimate the extent of genetic variability and relation between yield and related characters of rice. Forty Boro rice germplasm were evaluated in a randomised complete block design with three replications. Analysis of variance indicated significant differences among the genotypes for 14 quantitative characters. The presence of slightly higher phenotypic coefficient of variation than genotypic coefficient of variation indicated the negligible influence of environment on the expression of yield and its component traits. Leaf length, days to flowering, days to maturity and 1000 grain weight showed highly positive significant correlation present with yield hill-1. High heritability had been observed for yield contributing traits during the study, suggested that these traits would respond to selection owing to their high genetic variability and transmissibility. Therefore, a thorough understanding of the inheritance of traits, their heritability and relationship with other important characteristics is important for the choice of breeding and selection methods for crop improvement. Bangladesh Rice j. 2018, 22(1): 35-43